2017
DOI: 10.2139/ssrn.3053535
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English as an International/Lingua Franca or Mainstream Standard Language? Unheard Voices from the Classroom

Abstract: Over the last two decades there has been an upsurge in the voices among TESOL/applied linguistics scholars calling for the teaching of English as an International (EIL) and Lingua Franca (ELF) language as opposed to the mainstream Standard English (MSE). These calls seem to be rather theoretical than empirical intellectual debates among those scholars without taking on board the voices of English as a foreign language (EFL) teachers and learners themselves as stakeholders. Focusing on a Sudanese EFL context, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…He described the professional language skills required to teach English through English, exploring the relationship between language ability and teaching ability [1]. Alhassan suggested that in the past two decades, there has been a surge in TESOL/applied languages calling for English as an international teaching [2]. Polat aims to design a scale to test teachers' attitudes towards the role of grammar in the English teaching process and to find out the reliability and validity of the designed scale and other psychometric qualities [3].…”
Section: Related Workmentioning
confidence: 99%
“…He described the professional language skills required to teach English through English, exploring the relationship between language ability and teaching ability [1]. Alhassan suggested that in the past two decades, there has been a surge in TESOL/applied languages calling for English as an international teaching [2]. Polat aims to design a scale to test teachers' attitudes towards the role of grammar in the English teaching process and to find out the reliability and validity of the designed scale and other psychometric qualities [3].…”
Section: Related Workmentioning
confidence: 99%
“…If they are the same, then it can be called record and repeat [16,17]. Multimedia technology includes operating functions such as exchange, processing, and synthesis, which greatly enhances the expressiveness of information [18] (2) Information integration is conducive to the cultivation of students' comprehensive language ability. The core of traditional Chinese teaching is paperbased teaching materials [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…To sum up, the research-based intelligent educational environment provides a variety of technical conditions for English listening and speaking teaching. It includes voice environment, differentiated interaction, and timely feedback [11]. The interactive mode of English translation listening and speaking teaching is shown in Figure 2.…”
Section: Improved Image Restoration Algorithm Andmentioning
confidence: 99%